Effects of dietary minerals deficiency and supplementation on different parts of muscle minerals content in grazing Mongolian sheep - Meng, Lingbo; Jin, Xiwei; Qi, Zhi; Mi, Lan (Frontiers in Veterinary Science, 2024)
Objective The objective of this study was to investigate the impact of dietary deficiency and supplementation of calcium, zinc, copper, cobalt, manganese or selenium on minerals content in the longissimus dorsi (LD), biceps femoris (BF) and triceps brachii (TB) of grazing Mongolian sheep. Methods We randomly divided 98 sheep into 7 treatment groups and fed them specific diets for 60 days: a total mineral nutrition diet (LCG), a calcium deficiency diet (LCa), a zinc deficiency diet (LZn), a copper deficiency diet (LCu), a cobalt deficiency diet (LCo), a manganese deficiency diet (LMn) and a selenium deficiency diet (LSe). Then 7 sheep from each group were slaughtered and samples of LD, BF and TB were collected for mineral content analysis. The remaining sheep in each group were subsequently fed specific diets for an additional 41 days: a total mineral nutrition diet (SCG), a calcium supplementation diet (SCa), a zinc supplementation diet (SZn), a copper supplementation diet (SCu), a cobalt supplementation diet (SCo), a manganese supplementation diet (SMn) and a selenium supplementation diet (SSe). Afterward, all sheep were slaughtered, and muscle samples were collected and analyzed. Results Significant findings emerged that LCa decreased sulfur (S) content in BF and increased Ca content in LD and BF, while SCa increased S and Ca content in BF and TB, respectively (P < 0.05). LZn decreased Zn, S, and potassium (K) content in LD and BF, while SZn increased Zn and S content in LD and BF, respectively (P < 0.05). LCu decreased Cu and iron (Fe) content in LD and TB, while SCu increased Fe content in TB (P < 0.05). LCo decreased phosphorus, S, K, Ca, Mn, Fe, Cu, and Zn content in LD (P < 0.05). LMn decreased Mn content and increased K content in TB, while SMn decreased K content in BF and TB (P < 0.05). LSe and SSe decreased and increased Se content in LD, BF, and TB, respectively (P < 0.05). Conclusion Dietary mineral levels have varying effects on lamb meat minerals content. It is important to ensure an adequate intake of minerals in the diet to enhance the mineral nutrition of lamb meat.